SISTEM OPTIMALISASI DAYA SERAP AIR TANAH - Lumbantobing, Mangasa Paruhum; Siahaan, Gerson Valdo; Rosanti, Ari (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Indonesia has been experiencing water crisis despite its large natural sources. The eastern part of Indonesia suffer more than other areas. This activity is proposing what so called rainfall water trap that can be used for irrigation and domestic needs when dry season is coming. The approach used to realize the program is technology application in the form of development of rainfall water trap. The program can be utilized by involving people or community in the area that is perceived to have water scarcity problem during the dry season.